THE EXISTENCE OF TECHNOCRATS IN THE FORMULATION OF REGIONAL EDUCATION POLICIES IN SAMPANG REGENCY - Sirojuddin, Muhammad; Nurani, Farida; Sarwono, Sarwono (Faculty of Administrative Science, Universitas Brawijaya, 2024)
This study was conducted with the aim of knowing and analyzing the existence of technocrats in the formulation of regional education policy in Sampang Regency. As for the stages of policy formulation as stated Winarno (2014: 123) include the formulation of the problem (defining problem), policy agenda, to the selection of Policy Alternatives. Analysis in this study was conducted using qualitative research with descriptive approach. The results of the study when viewed from the context of the formulation of the problem shows that there are still unevenness educational facilities causes low quality of Education, high dropout rates, and low participation society. Technocrats have formulated several efforts to answer these problems such as equitable distribution of educational facilities in elementary schools but not yet equitable in high schools, data collection and socialization of the causes of school dropout rates, and creating Community Learning Center (PKBM) programs to reduce the low average Community School duration. At the stage of identifying alternative policies, technocrats offered several recommendations to improve Sampang Regency education, namely conducting data collection related to school dropout rates, improving quality by making certain advantages in each school, building educational history buildings, increasing cooperation between Pondok pesantren salafiyah and PKBM, and pesantren should be recognized as formal education.